2021
DOI: 10.1115/1.4052097
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Fundamental Combustion Properties of Oxymethylene Ether-2

Abstract: Oxymethylene ethers (OMEn, n=1-5) are a promising class of synthetic fuels that have the potential to be used as diesel additives or substitutes. A comprehensive understanding of their combustion properties is required for their safe and efficient utilization. In this study, a combined experimental and modeling work on oxidation of OME2 is reported: (i) Ignition delay time measurements of stoichiometric OME2 / synthetic air mixtures diluted 1:5 with nitrogen using the shock tube method at pressures of 1, 4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Sun et al [7] have measured the LBV of OME 3 at 408 K and 1 atm with the peak value found at ϕ = 1.2 as well. The same findings were observed within the different studies of OME 2 from Eckart et al [8] and Ngugi et al [9], who have presented LBV values at various temperatures and pressures ranging, in total, from 383 K to 473 K and from 1 bar to 6 bar.…”
Section: Results Of the Laminar Burning Velocitysupporting
confidence: 86%
See 2 more Smart Citations
“…Sun et al [7] have measured the LBV of OME 3 at 408 K and 1 atm with the peak value found at ϕ = 1.2 as well. The same findings were observed within the different studies of OME 2 from Eckart et al [8] and Ngugi et al [9], who have presented LBV values at various temperatures and pressures ranging, in total, from 383 K to 473 K and from 1 bar to 6 bar.…”
Section: Results Of the Laminar Burning Velocitysupporting
confidence: 86%
“…To the best of our knowledge, experimental LBV data of OME 4 are presented for the first time; thus, allowing only for a comparison to literature data with other OME n . In general, measurements of higher OME n (n ≥ 2) have been published by Sun et al [7], Eckart et al [8], and Ngugi et al [9]. Sun et al [7] have measured the LBV of OME 3 at 408 K and 1 atm with the peak value found at ϕ = 1.2 as well.…”
Section: Results Of the Laminar Burning Velocitymentioning
confidence: 96%
See 1 more Smart Citation
“…As a consequence, the position of the reaction zone is moving to larger distances with decreasing chain length [51]. Indeed, the laminar flame speed is found to increase with the OME chain length [15,16,52,53]. This is even more obvious when the CH2O peak maxima, one of the first species formed (see Fig.…”
Section: Main Speciesmentioning
confidence: 89%
“…Following up to Sun et al, He and coworkers provided another model for OME3 [14].. Focusing on OME2, Ngugi et al have studied laminar flame speed as well as ignition delay times and autoignition of OME2 [15]. They have shown similar oxidation pathways for OME2 and OME1.…”
Section: Introductionmentioning
confidence: 99%